C-NODDI: a constrained NODDI model for axonal density and orientation determinations in cerebral white matter - Alsameen, Maryam H.; Gong, Zhaoyuan; Qian, Wenshu; Kiely, Matthew; Triebswetter, Curtis; Bergeron, Christopher M.; Cortina, Luis E.; Faulkner, Mary E.; Laporte, John P.; Bouhrara, Mustapha (Frontiers in Neurology, 2023)
Purpose: Neurite orientation dispersion and density imaging (NODDI) provides measures of neurite density and dispersion through computation of the neurite density index (NDI) and the orientation dispersion index (ODI). However, NODDI overestimates the cerebrospinal fluid water fraction in white matter (WM) and provides physiologically unrealistic high NDI values. Furthermore, derived NDI values are echo-time (TE)-dependent. In this work, we propose a modification of NODDI, named constrained NODDI (C-NODDI), for NDI and ODI mapping in WM. Methods: Using NODDI and C-NODDI, we investigated age-related alterations in WM in a cohort of 58 cognitively unimpaired adults. Further, NDI values derived using NODDI or C-NODDI were correlated with the neurofilament light chain (NfL) concentration levels, a plasma biomarker of axonal degeneration. Finally, we investigated the TE dependence of NODDI or C-NODDI derived NDI and ODI.Results: ODI derived values using both approaches were virtually identical. Further, our results indicated a quadratic relationship between NDI and age suggesting that axonal maturation continues until middle age followed by a decrease. This quadratic association was notably significant in several WM regions using C-NODDI, while limited to a few regions using NODDI.ODI exhibited overall constant trends with age. Further, C-NODDI-NDI values exhibited a stronger correlation with NfL concentration levels as compared NODDI-NDI, with lower NDI values corresponding to higher levels of NfL. Finally, we confirmed the previous finding that NDI estimation using NODDI was dependent on TE, while NDI derived values using C-NODDI exhibited lower sensitivity to TE in WM.C-NODDI provides a complementary method to NODDI for determination of NDI in white matter in normative aging.